Given that
and ![f(n)=[f(n-1)]^2-n](https://tex.z-dn.net/?f=f%28n%29%3D%5Bf%28n-1%29%5D%5E2-n)
We need to determine the value of f(4)
To determine the value of f(4), we need to know the values of the previous terms f(2), f(3).
<u>The value of f(2):</u>
The value of f(2) can be determined by substituting n = 2 in the function ![f(n)=[f(n-1)]^2-n](https://tex.z-dn.net/?f=f%28n%29%3D%5Bf%28n-1%29%5D%5E2-n)
Thus, we get;
![f(2)=[f(2-1)]^2-2](https://tex.z-dn.net/?f=f%282%29%3D%5Bf%282-1%29%5D%5E2-2)
![f(2)=[f(1)]^2-2](https://tex.z-dn.net/?f=f%282%29%3D%5Bf%281%29%5D%5E2-2)


Thus, the value of f(2) is 2.
<u>The value of f(3):</u>
The value of f(3) can be determined by substituting n = 3 in the function ![f(n)=[f(n-1)]^2-n](https://tex.z-dn.net/?f=f%28n%29%3D%5Bf%28n-1%29%5D%5E2-n)
Thus, we get;
![f(3)=[f(3-1)]^2-3](https://tex.z-dn.net/?f=f%283%29%3D%5Bf%283-1%29%5D%5E2-3)
![f(3)=[f(2)]^2-3](https://tex.z-dn.net/?f=f%283%29%3D%5Bf%282%29%5D%5E2-3)


Thus, the value of f(3) is 1.
<u>The value of f(4):</u>
The value of f(4) can be determined by substituting n = 4 in the function ![f(n)=[f(n-1)]^2-n](https://tex.z-dn.net/?f=f%28n%29%3D%5Bf%28n-1%29%5D%5E2-n)
Thus, we get;
![f(4)=[f(4-1)]^2-4](https://tex.z-dn.net/?f=f%284%29%3D%5Bf%284-1%29%5D%5E2-4)
![f(4)=[f(3)]^2-4](https://tex.z-dn.net/?f=f%284%29%3D%5Bf%283%29%5D%5E2-4)


Thus, the value of f(4) is -3.